PEMBELAJARAN NILAI NILAI KARAKTER ISLAM MODERAT DI PERGURUAN TINGGI - Gusnarib (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2018)
This study discusses how to integrate the values ​​of moderate Islamic character in Islamic higher education institutions. Integration of the value of moderate Islamic character values ​​can be implemented through learning in all subjects in Islamic higher education. Integration of Islamic character values ​​can be done on all subjects in Islamic higher education by referring to the concepts, systems and theories of learning. Learning the value of moderate Islamic characters can give students a personality color better than before and can inspire lecturers as learners. in carrying out enlightenment and intelligence in shaping tough, courageous, honest, tolerant, responsible and consistent students, in order to answer the challenges of powerlessness and inability to build national identity, inability to reconstruct the nation's potential responsively and dynamically. The hope of the writer, with the integration of the value of moderate Islamic character in all courses in Islamic higher education, can be the basis for the formation of adherent behavior, and the value of character can be a declarator of glory on the face of the earth